1983
DOI: 10.1097/00132586-198308000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halothane on Coronary Haemodynamics and Myocardial Metabolism in Patients with Ischaemic Heart Disease and Heart Failure

Abstract: Halothane was administered at an end-tidal concentration of 1 % to 10 patients with stable ischaemic heart disease and clinical and haemdynamic signs of moderate heart failure. Measurements of central haeniodynamic variables, coronary sinus blood flow and oxygen, lactate and hypoxanthine balances over the myocardium were done before and at steady state during halothane anaesthesia. Halothane induced marked haemodynamic changes with decreases in mean arterial pressure (-43 %), mean pulmonary arteriolar occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Coronary sinus blood flow was determined by the continuous retrograde thermodilution technique, using room temperature normal saline as the indicator, injected at approximately 40 ml/min during 15-20 s for each measurement. All methods for pressure and flow measurements have previously been described in detail (7). Blood was sampled simultaneously from the artery, pulmonary artery and the coronary sinus for determination of oxygen content (13), lactate concentration (14) and adrenaline-noradrenaline concentrations (15) at each measurement period.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary sinus blood flow was determined by the continuous retrograde thermodilution technique, using room temperature normal saline as the indicator, injected at approximately 40 ml/min during 15-20 s for each measurement. All methods for pressure and flow measurements have previously been described in detail (7). Blood was sampled simultaneously from the artery, pulmonary artery and the coronary sinus for determination of oxygen content (13), lactate concentration (14) and adrenaline-noradrenaline concentrations (15) at each measurement period.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the same authors noted decreased cardiac index, systemic vascular resistance, coronary sinus blood flow, myocardial oxygen consumption and no myocardial lactate production in aortic vascular surgery patients with coronary artery disease and evidence of heart failure using one per cent end-tidal halothane in 30 per cent oxygen . 220 The authors suggested that unloading of the left ventricle by systemic vasodilatation predominates over the cardiac-depressant action of halothane in this patient population.…”
Section: Anaesthetic Techniquementioning
confidence: 96%
“…These effects, in combination with unchanged myocardial lactate metabolism, indicate that halothane preserves myocardial oxygen balance in patients with CAD (1)(2)(3)(4). These effects, in combination with unchanged myocardial lactate metabolism, indicate that halothane preserves myocardial oxygen balance in patients with CAD (1)(2)(3)(4).…”
mentioning
confidence: 99%